Simvastatin Enhances the Immune Response Against Mycobacterium tuberculosis - Guerra-De-Blas, Paola Del Carmen; Bobadilla-Del-Valle, Miriam; Sada-Ovalle, Isabel; Estrada-García, Iris; Torres-González, Pedro; López-Saavedra, Alejandro; Guzmán-Beltrán, Silvia; Ponce-de-León, Alfredo; Sifuentes-Osornio, José (Frontiers in Microbiology, 2019)
Tuberculosis remains a serious threat worldwide. For this reason, it is necessary to identify agents that shorten the duration of treatment, strengthen the host immune system, and/or decrease damage caused by the infection. Statins are drugs that reduce plasma cholesterol levels and also have immunomodulatory, anti-inflammatory and antimicrobial effects. Although there is evidence that statins may contribute to the containment of Mycobacterium tuberculosis infection, their effects on peripheral blood mononuclear cells (PBMCs) involved in the immune response has not been previously described. Using PBMCs, from ten healthy subjects, that were infected with M. tuberculosis H37Rv, we analysed the effects of simvastatin on the treatment of infection in an in vitro experimental model. Direct quantification of M. tuberculosis growth in CFU/mL was performed. Phenotype and cell activation were assessed by multi-color flow cytometry. Cytokines levels were determined in culture supernatant by cytokine bead arrays. Induction of apoptosis and autophagy were evaluated by flow cytometry and confocal microscopy. Simvastatin decreased the growth of M. tuberculosis in PBMCs, increased the proportion of NKT cells in culture, increased the expression of co-stimulatory molecules in monocytes, promoted the secretion of the cytokines IL-1β and IL-12p70, and activated apoptosis and autophagy in monocytes, which resulted in a significant reduction of the bacterial load. We also observed an increase in the production of IL-10. We did not observe direct antimycobacterial activity. This study provides new insights into the immune correlates that how simvastatin reduce the mycobacterial load in infected PBMCs. These results demonstrate that simvastatin activates several immune mechanisms that favour the containment of M. tuberculosis infection, providing relevant evidence to consider statins as candidates for host-directed therapy. It also opens the need of future studies to define the role of anti-inflammatory mechanisms induced by statins in the therapy of tuberculosis.